The Role of Moral Injury in PTSD Among Law Enforcement Officers: A Brief Report - Papazoglou, Konstantinos; Blumberg, Daniel M.; Chiongbian, Victoria Briones; Tuttle, Brooke McQuerrey; Kamkar, Katy; Chopko, Brian; Milliard, Beth; Aukhojee, Prashant; Koskelainen, Mari (Frontiers in Psychology, 2020)
Exposure to critical incidents and hence potentially traumatic events is endemic in law enforcement. The study of law enforcement officers’ experience of moral injury and their exposure to potentially morally injurious incidents, and research on moral injury’s relationship with different forms of traumatization (e.g., compassion fatigue, posttraumatic stress disorder) are in their infancy. The present study aims to build on prior research and explores the role of moral injury in predicting posttraumatic stress disorder (PTSD) and its clusters thereof. To this end, a sample of law enforcement officers (N = 370) from the National Police of Finland was recruited to participate in the current study. Results showed that moral injury significantly predicted PTSD as well as its diagnostic clusters (i.e., avoidance, hyperarousal, re-experiencing). The aforementioned role of moral injury to significantly predict PTSD and its clusters were unequivocal even when compassion fatigue was incorporated into the path model. Clinical, research, and law enforcement practice implications are discussed.